Composite sheet, inner container, cooking utensil and manufacturing method of composite sheet
By forming grooves on the surface of the metal matrix of the composite sheet and attaching a coating with a columnar nanocrystal structure, the problem that the traditional coating is easy to fall off at high temperatures is solved, and the composite sheet has high wear resistance, corrosion resistance and use. Improvement of lifespan.
Patent Information
- Application Number
- CN202310882161.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-21
AI Technical Summary
When existing composite sheets are used at high temperatures, the traditional inner liner coating is prone to fall off, and it is not sticky and corrosion-resistant, resulting in a short service life.
The surface of the metal substrate is used to form grooves through laser processing to form a concave and convex marking area, and a coating with a columnar nanocrystal structure is attached to the surface through physical vapor deposition to improve its wear resistance and corrosion resistance.
This method has significantly improved the abrasion resistance, corrosion resistance and service life of complex sheets without increasing complex processes and costs, while maintaining the shape and aesthetics of the uneven identification area.
Smart Images

Figure CN119332204A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of composite materials, and in particular to a composite sheet, an inner pot, a cooking utensil, and a method for manufacturing the composite sheet. Background Art
[0002] In order to make the composite sheet easy to clean and extend its service life, an attachment coating is usually used. Common coating materials include fluororesin non-stick coating and ceramic coating, among which the non-stick coating has excellent non-stick and corrosion resistance, but low hardness, poor bonding with the substrate, easy to fall off, and may release harmful substances such as PFOA (perfluorooctanoic acid) at high temperatures, while the ceramic non-stick coating has poor water resistance and deteriorates in non-stick properties after long-term use. Therefore, hard PVD (physical vapor deposition) coating is currently used to replace the traditional liner coating. Usually, the logo is solidified on the surface of the coating by traditional pad printing on the surface after the PVD coating is attached. After pad printing, it needs to be cured by heating and drying, etc. The process is complicated, the cost is high, and the efficiency is low. In addition, the pad-printed logo has poor adhesion due to the lack of coating protection, and is easy to wear and fall off during use.
[0003] Therefore, a composite sheet, an inner pot, a cooking utensil and a method for manufacturing the composite sheet are needed to at least partially solve the above problems. Summary of the invention
[0004] A series of simplified concepts are introduced in the content section of this application, which will be further described in detail in the detailed implementation section. The content section of this application does not mean to attempt to define the key features and essential technical features of the technical solution claimed for protection, nor does it mean to attempt to determine the scope of protection of the technical solution claimed for protection.
[0005] In order to at least partially solve the above problems, the first aspect of the present application provides a composite sheet, comprising:
[0006] A metal substrate, wherein a surface of the metal substrate has a plurality of grooves extending along a first direction, wherein the plurality of grooves are periodically arranged along a second direction to form a concave-convex marking area, wherein the second direction is different from the first direction, and wherein the grooves are formed into the concave-convex marking area by laser processing;
[0007] The coating is attached to the surface of the metal substrate by physical vapor deposition and covers the concave-convex marking area, wherein the coating includes a surface layer, and the surface layer is constructed as a columnar nanocrystal structure layer grown by physical vapor deposition.
[0008] According to the present application, the coating formed by physical vapor deposition attached to the surface of the metal substrate will not change the structure of the groove, and the shape of the concave-convex marking area can still be maintained. The coating can also protect the concave-convex marking area, improve its wear resistance and corrosion resistance, and increase its service life.
[0009] Preferably, the depth of the groove before the coating is attached is greater than the depth of the groove after the coating is attached; and / or
[0010] The depth of the groove before the coating is attached is 5-20 μm, and the depth of the groove after the coating is attached is 4-19 μm.
[0011] According to the present application, grooves of a specific size can form a light trap effect, directly reflecting and scattering light, thereby making the concave and convex logo area appear matte black, and the depth of the groove becomes smaller after the coating is attached, making the light trap effect more obvious.
[0012] Preferably, the cross-section of the concave-convex marking area is configured in a tooth shape, and a spacer is formed between two adjacent grooves.
[0013] According to the present application, the concave-convex marking area of a specific shape makes its processing simple, efficient, and improves the aesthetics.
[0014] Preferably, the width of the groove before the coating is attached is greater than the width after the coating is attached, and the width of the spacer before the coating is attached is smaller than the width after the coating is attached.
[0015] According to the present application, the width of the groove becomes smaller after being coated, and the width of the spacer becomes larger after being coated, so that the light trap effect is more obvious.
[0016] Preferably, the width of the groove before the coating is attached is 5-30 μm, and the width of the groove after the coating is attached is 4-28 μm;
[0017] The width of the spacer before being attached to the coating film is 5-30 μm, and the width of the spacer after being attached to the coating film is 7-32 μm.
[0018] According to the present application, grooves of a specific size can form a light trap effect, directly reflecting and scattering light, so that the concave and convex marking area appears matte black, and the width of the groove becomes smaller after being attached with a coating, and the width of the spacer becomes larger after being attached with a coating, making the light trap effect more obvious.
[0019] Preferably, the cross-section of the concave-convex marking area is wavy, and the distances between adjacent wave peaks are equal before and after the coating is attached.
[0020] According to the present application, the concave-convex marking area of a specific shape makes its processing simple, efficient, and improves the aesthetics.
[0021] Preferably, the distance between adjacent wave peaks is 5-30 μm.
[0022] According to the present application, grooves of a specific size can form a light trap effect, directly reflecting and scattering light, thereby making the concave-convex logo area appear matte black.
[0023] Preferably, the surface roughness of the metal substrate is 0.1-0.8 μm.
[0024] According to the present application, the smooth metal substrate surface has a strong bonding force with the coating, so that the coating is not easy to fall off from the metal substrate surface, resulting in a continuous protective effect, and the smoother it is, the easier it is to clean.
[0025] Preferably, the columnar nanocrystal structure in the surface layer has a plurality of crystal grains growing in a columnar shape, and the side surfaces of the plurality of crystal grains are bonded to each other. When the surface layer is at a predetermined thickness, the top ends of the crystal grains grow to form protrusions, so that the surface structure of the surface layer is a nano-scale concave-convex structure.
[0026] According to the present application, the nano-scale concave-convex structure formed on the coating surface cooperates with the concave-convex marking area on the metal substrate surface to form a double concave-convex structure, further improving the wear resistance and non-stickiness of the composite sheet.
[0027] Preferably, the radial size of the grains is 20-80 nm; and / or
[0028] The predetermined thickness of the surface layer is 100-600 nm.
[0029] According to the present application, a nanoscale dimension can be provided for the surface of the coating to form a special columnar nanocrystal structure.
[0030] Preferably, the coating further includes a transition layer, the surface layer is attached to the transition layer, the transition layer includes a first transition layer and a second transition layer, and the first transition layer and the second transition layer are alternately stacked.
[0031] According to the present application, the growth of the surface layer on the transition layer can improve the density of the surface layer, thereby improving the hardness and corrosion resistance.
[0032] Preferably, the coating further comprises a bottom layer, the bottom layer is attached to the surface of the metal substrate, the transition layer is attached to the bottom layer, and the bottom layer is a metal layer.
[0033] According to the present application, the metal bottom layer can increase the bonding force between the coating and the metal substrate, making it difficult for the coating to fall off from the metal substrate, thereby increasing the service life.
[0034] Preferably, the thickness of the first transition layer is 10-50 nm, the thickness of the second transition layer is 10-50 nm, and the total thickness of the transition layers is 300-1000 nm; and / or
[0035] The thickness of the bottom layer is 100-500 nm; and / or
[0036] The total thickness of the coating is 700-2000nm.
[0037] According to the present application, the thickness of each layer is reasonably set, which further improves the wear resistance and corrosion resistance of the coating.
[0038] Preferably, the surface layer is a titanium carbonitride layer, a chromium carbonitride layer or a zirconium carbonitride layer.
[0039] According to the present application, the specific surface material can enable the surface layer to grow into columnar nanocrystals, further improving the wear resistance and corrosion resistance of the composite sheet.
[0040] Preferably, the surface layer is a titanium carbonitride-copper composite layer, a chromium carbonitride-copper composite layer or a zirconium carbonitride-copper composite layer.
[0041] According to the present application, since copper does not react with carbon and nitrogen elements, nor can it form a solid solution with carbonitrides, but exists in an amorphous form, adding copper elements to the surface layer can effectively reduce the surface energy and further improve the wear resistance and corrosion resistance of the composite sheet.
[0042] Preferably, amorphous copper is coated outside the grains of the columnar nanocrystalline structure.
[0043] According to the present application, copper can inhibit the growth of grains, so the grains will be smaller, effectively reducing the surface energy, and further improving the wear resistance and corrosion resistance of the composite sheet.
[0044] Preferably, the first transition layer is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer;
[0045] The second transition layer is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer;
[0046] The second transition layer is different from the first transition layer.
[0047] According to the present application, a transition layer formed by alternating two material layers formed by titanium, chromium and zirconium base and their compounds can produce a template effect on the growth of columnar nanocrystalline structure, causing lattice distortion, inhibiting the growth of coarse columnar nanocrystals on the surface, and making the columnar grains tend to grow perpendicular to the crystal plane, thereby reducing the surface energy of the surface layer, forming a fine and dense columnar nanocrystalline structure, so that the composite sheet has good non-stickiness and easy cleaning properties, and as the density of the surface layer increases, its hardness and corrosion resistance are also improved.
[0048] Preferably, the bottom layer is a titanium metal layer, a chromium metal layer, a zirconium metal layer, a chromium-titanium composite metal layer, a chromium-zirconium composite metal layer or a zirconium-titanium composite metal layer.
[0049] According to the present application, the metal base layer and the transition layer contain the same metal element, which can increase the bonding strength between the base layer and the transition layer and further increase the service life.
[0050] A second aspect of the present application provides an inner liner, which includes the composite sheet according to any one of the above technical solutions.
[0051] According to the present application, it is made of the composite sheet material described in the first aspect above, and therefore has a technical effect similar to that of the composite sheet material of the first aspect above.
[0052] A third aspect of the present application provides a cooking utensil, comprising:
[0053] A pot body, wherein the pot body is provided with the inner pot according to the above technical solution;
[0054] The cover body is openably and closably arranged on the pot body. When the cover body covers the pot body, a cooking space is formed between the cover body and the inner pot.
[0055] According to the present application, the inner liner of the second aspect described above has a technical effect similar to that of the inner liner of the second aspect described above.
[0056] A fourth aspect of the present application provides a method for manufacturing a composite sheet, the method comprising:
[0057] The step of preparing a metal substrate comprises:
[0058] The step of forming the concave-convex marking area is as follows: a plurality of grooves extending along a first direction are arranged on the surface of the metal substrate, the plurality of grooves are periodically arranged along a second direction to form the concave-convex marking area, the second direction is different from the first direction, the grooves are formed into the concave-convex marking area by laser processing,
[0059] placing the metal substrate in a physical vapor deposition apparatus;
[0060] The physical vapor deposition step deposits a coating at least at the concave-convex marking area of the metal substrate, and the physical vapor deposition step includes a surface deposition step: the surface layer of the coating is grown into a columnar nanocrystalline structure by physical vapor deposition.
[0061] According to the present application, the combination of the concave-convex identification area and the columnar nanocrystal PVD coating of the composite sheet prepared by this manufacturing method can make the composite sheet have good non-stick, hydrophobic and easy-to-clean properties without setting a special non-stick coating, and also have high hardness and scratch resistance; the columnar nanocrystal structure can be directly formed on the surface of the metal substrate through physical vapor deposition without the need for additional steps.
[0062] Preferably, the laser processing uses picosecond laser pulses or nanosecond laser pulses.
[0063] According to the present application, a more reasonable process can be adopted to make the laser processing more efficient.
[0064] Preferably, the laser power is set to 10-100 W, the scanning speed is set to 100-3000 mm / s, and / or
[0065] The laser processing adopts an arcuate filling method.
[0066] According to the present application, a more reasonable process can be adopted to make the laser processing more efficient.
[0067] Preferably, the step of preparing the metal substrate further comprises a polishing step and a cleaning step before the step of forming the concave-convex marking area, wherein the metal substrate is polished and cleaned so that the surface roughness of the metal substrate is 0.1-0.8 μm.
[0068] According to the present application, the surface roughness of the metal substrate can be reduced by polishing. The smooth metal substrate surface has a stronger bonding force with the coating, making it difficult for the coating to fall off the metal substrate surface, producing a continuous protective effect, and the smoother it is, the easier it is to clean.
[0069] Preferably, the metal substrate is polished by mechanical polishing, electrochemical polishing or plasma polishing, and then the polished surface is subjected to wire drawing, followed by ultrasonic cleaning, pure water cleaning and drying.
[0070] According to the present application, the expected roughness can be obtained.
[0071] Preferably, a deposition furnace of the physical vapor deposition device is provided with a rotating frame, a first metal target and a second metal target different from the first metal target, wherein the first metal target and the second metal target are arranged at intervals around the rotation axis of the rotating frame, the metal elements of the first metal target and the second metal target are selected from titanium, chromium or zirconium, and the physical vapor deposition device further has a carbon source and a nitrogen source;
[0072] The step of preparing the metal substrate comprises: placing the metal substrate on the rotating frame and making the surface to be deposited of the metal substrate face away from the rotating axis;
[0073] The step of depositing the surface layer also includes: opening one of the first metal target and the second metal target, opening a carbon source and a nitrogen source, and depositing the surface layer on the surface to be deposited of the metal substrate, wherein the metal element of the first metal target or the second metal target reacts with the carbon source and the nitrogen source to form the surface layer.
[0074] According to the present application, a columnar nanocrystalline surface layer of carbonitride can be grown on the surface of a metal substrate through a PVD process.
[0075] Preferably, the physical vapor deposition step also includes a transition layer deposition step, and the transition layer deposition step is located before the surface layer deposition step, and the transition layer deposition step includes: opening the first metal target and the second metal target, and alternately depositing the first transition layer and the second transition layer on the surface to be deposited of the metal substrate by rotation, wherein the metal elements of the first metal target react with the carbon source and the nitrogen source to form a first transition layer, and the metal elements of the second metal target react with the carbon source and the nitrogen source to form a second transition layer.
[0076] According to the present application, a transition layer formed by alternating two material layers formed by titanium, chromium and zirconium base and their compounds can produce a template effect on the growth of a columnar nanocrystal structure, causing lattice distortion, inhibiting the growth of coarse columnar nanocrystals on the surface, and making the columnar grains tend to grow perpendicular to the crystal plane, thereby reducing the surface energy of the surface layer, forming a fine and dense columnar nanocrystal structure, so that the composite sheet has good non-stickiness and easy cleaning properties, and as the density of the surface layer increases, its hardness and corrosion resistance are also improved; by rotating the metal substrate to be alternately covered by the coating material produced by the first metal target and the second metal target, an alternating first transition layer and a second transition layer can be efficiently formed.
[0077] Preferably, the physical vapor deposition step also includes a bottom layer deposition step, which is located before the transition layer deposition step, and the bottom layer deposition step includes: opening the first metal target and / or the second metal target, closing the nitrogen source and the carbon source, continuously introducing argon gas into the deposition furnace, and depositing a metal bottom layer on the surface to be deposited of the metal substrate.
[0078] According to the present application, the metal base layer can be deposited using the same PVD equipment, and the metal base layer can increase the bonding strength between the coating and the metal substrate, making the coating less likely to fall off the metal substrate, thereby increasing the service life.
[0079] Preferably, the carbon source is acetylene gas, and the nitrogen source is nitrogen gas;
[0080] The step of depositing the surface layer also includes: setting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, setting the temperature of the deposition furnace to 280-300°C, applying a bias voltage of 140-160V to the metal substrate during deposition, and depositing for 10-30 minutes to control the thickness of the surface layer to 100-600nm.
[0081] According to the present application, a more reasonable process parameter setting can obtain a surface layer with a specific thickness, further improving the hardness, bonding strength and corrosion resistance of the coating.
[0082] Preferably, the carbon source is acetylene gas, and the nitrogen source is nitrogen gas;
[0083] The step of depositing the transition layer also includes: setting the temperature of the deposition furnace to 240-260°C, setting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, applying a bias voltage of 140-160V to the metal substrate during deposition, and depositing for 20-60 minutes to control the thickness of the transition layer to 300-1000nm.
[0084] According to the present application, the process parameters are set more reasonably, further improving the hardness, bonding strength and corrosion resistance of the coating.
[0085] Preferably, the deposited bottom layer also includes: setting the temperature of the deposition furnace to 200-450°C, glow cleaning the metal substrate for 3-7 minutes before deposition, applying a bias voltage of 50-250V to the metal substrate during deposition, and depositing for 5-15 minutes to control the thickness of the bottom layer to 100-500nm.
[0086] According to the present application, the process parameters are set more reasonably, further improving the hardness, bonding strength and corrosion resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0087] The following drawings of the present application are used as a part of the present application for understanding the present application. The drawings show the implementation modes of the present application and the description thereof, and are used to explain the principle of the present application.
[0088] In the attached figure:
[0089] Figure 1It is a partial cross-sectional schematic diagram of a composite sheet before being coated according to a preferred embodiment of the present application;
[0090] Figure 2 for Figure 1 A partial cross-sectional schematic diagram of a composite sheet after coating is attached;
[0091] Figure 3 It is a partial cross-sectional schematic diagram of a composite sheet before being coated according to another embodiment of the present application;
[0092] Figure 4 for Figure 3 A partial cross-sectional schematic diagram of a composite sheet after coating is attached;
[0093] Figure 5 It is a schematic cross-sectional view of the composite sheet material according to the present application in the non-concave-convex marking area;
[0094] Figure 6 A more detailed schematic cross-sectional structure diagram of a coating of a composite sheet according to an embodiment of the present application;
[0095] Figure 7a-7d It is a schematic diagram of the cross-sectional structure of the surface layer of the coating according to the present application at different growth thicknesses;
[0096] Figure 8 is a top cross-sectional schematic diagram of a physical vapor deposition device according to an embodiment of the present application;
[0097] Fig. 9 is a side cross-sectional schematic diagram of a physical vapor deposition device according to an embodiment of the present application;
[0098] Fig.10 A simplified flow chart of a method for manufacturing a composite sheet according to an embodiment of the present application;
[0099] Fig.11 A more detailed schematic flow chart of a method for manufacturing a composite sheet according to an embodiment of the present application.
[0100] Description of reference numerals:
[0101] 110: Metal matrix
[0102] 111: Groove
[0103] 112: Interval
[0104] 113: Crest
[0105] 120: Surface
[0106] 121: Grain
[0107] 122: Protrusion
[0108] 130: Transition layer
[0109] 131: First transition layer
[0110] 132: Second transition layer
[0111] 140: Bottom
[0112] 150: Coating
[0113] 10: Physical vapor deposition equipment
[0114] 11: Deposition furnace
[0115] 12: Rotating stand
[0116] 13: First metal target
[0117] 14: Second metal target DETAILED DESCRIPTION
[0118] In the following description, a large number of specific details are provided to provide a more thorough understanding of the present application. However, it is apparent to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features well known in the art are not described.
[0119] In order to thoroughly understand the present application, a detailed description will be provided in the following description. Obviously, the implementation of the embodiments of the present application is not limited to the specific details familiar to those skilled in the art. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other embodiments.
[0120] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should also be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of the features, wholes, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or combinations thereof.
[0121] Ordinal numbers such as “first” and “second” cited in the present application are merely identifications and do not have any other meanings, such as a specific order, etc. Moreover, for example, the term “first component” itself does not imply the existence of the “second component”, and the term “second component” itself does not imply the existence of the “first component”.
[0122] It should be noted that the terms "upper", "lower", "front", "back", "left", "right", "inside", "outside" and similar expressions used in this document are for illustrative purposes only and are not limiting.
[0123] Now, exemplary embodiments according to the present application will be described in more detail with reference to the accompanying drawings. However, these exemplary embodiments can be implemented in a variety of different forms and should not be interpreted as being limited to the embodiments described herein. It should be understood that these embodiments are provided to make the disclosure of the present application thorough and complete, and to fully convey the concepts of these exemplary embodiments to those of ordinary skill in the art.
[0124] The first aspect of the present application provides a composite sheet, such as Figure 1-4 As shown, the composite sheet includes a metal substrate 110 and a coating 150. The surface of the metal substrate 110 has a plurality of grooves 111 extending along a first direction, and the plurality of grooves 111 are periodically arranged along a second direction to form a concave-convex marking area. The second direction is different from the first direction. The grooves 111 are formed into a concave-convex marking area by laser processing. The coating 150 is attached to the surface of the metal substrate 110 by physical vapor deposition and covers the concave-convex marking area. The coating 150 includes a surface layer 120, and the surface layer 120 is constructed as a columnar nanocrystalline structure layer grown by physical vapor deposition. Preferably, the columnar nanocrystalline structure in the surface layer 120 has a plurality of crystal grains 121 growing in a columnar shape, and the side surfaces of the plurality of crystal grains 121 are attached to each other, and the radial dimension D of the crystal grains 121 is 20-80nm. According to this solution, a nanoscale dimension can be provided for the surface of the coating 150 to form a special columnar nanocrystalline structure.
[0125] According to the composite sheet of the present application, a coating formed by physical vapor deposition is attached to the surface of the metal substrate, which will not change the structure of the groove and can still maintain the shape of the concave-convex marking area. The coating can also protect the concave-convex marking area, improve its wear resistance and corrosion resistance, and increase its service life.
[0126] The above-mentioned nanoscale refers to a scale ranging from 1 to 100 nm.
[0127] Preferably, the metal substrate 110 can be made of stainless steel, aluminum alloy, titanium alloy, etc. For example, in one embodiment, the metal substrate 110 is made of a composite material of a 304 stainless steel layer and a low carbon steel layer, wherein the thickness of the stainless steel layer is greater than 0.1 mm, and the total thickness of the metal substrate 110 is greater than 1 mm.
[0128] The surface roughness of the metal substrate 110 is 0.1-0.8 μm. The surface of the metal substrate 110 is provided with grooves 111, but still has a relatively low surface roughness, so that the metal substrate 110 has a smooth surface, and the bonding force with the coating is strong, so that the coating is not easy to fall off from the surface of the metal substrate, and a continuous protective effect is produced, and the smoother it is, the easier it is to clean.
[0129] Specifically, the depth of the groove 111 before the coating 150 is attached is 5-20 μm. The depth of the groove 111 after the coating 150 is attached is 4-19 μm. Since the coating 150 has a certain thickness, the depth of the groove 111 before the coating 150 is attached is greater than the depth after the coating 150 is attached.
[0130] More specifically, if Figure 1 and Figure 2 As shown, in one embodiment, the cross-section of the concave-convex marking area can be configured as a tooth shape. A spacer 112 is formed between two adjacent grooves 111. In other words, the cross-sections of the grooves 111 and the spacer 112 are both rectangular, and the grooves 111 and the spacer 112 are alternately arranged along the second direction.
[0131] Figure 1 The metal substrate 110 is shown in a state before the coating film 150 is attached. At this time, the width of the groove 111 is 5-30 μm, and the width of the spacer 112 is 5-30 μm. Figure 2 The metal substrate 110 is shown in a state after being attached with the coating film 150, at which time the width of the groove 111 is 4-28 μm, and the width of the spacer 112 is 7-32 μm. In addition, due to the influence of the thickness of the coating film 150, the width of the groove 111 before being attached with the coating film 150 is greater than the width after being attached with the coating film 150, and the width of the spacer 112 before being attached with the coating film 150 is less than the width after being attached with the coating film 150.
[0132] like Figure 3 and Figure 4 As shown, in another embodiment, the cross-section of the concave-convex marking area is wavy, with grooves 111 and crests 113, and crests 113 are located between two adjacent grooves 111. In other words, the grooves 111 and crests 113 are alternately arranged along the second direction.
[0133] Since it is not affected by the thickness of the coating 150, the distance between adjacent peaks 113 is Figure 3 The attached coating 150 is shown before and Figure 4 The distance between the attached coating 150 shown may be 5-30 μm.
[0134] The surface layer 120 has a low surface energy characteristic, and the contact angle of water on the surface of the surface layer 120 is 80-110°.
[0135] Preferably, the surface layer 120 can be a titanium carbonitride layer, a chromium carbonitride layer or a zirconium carbonitride layer. The specific surface material can make the surface layer 120 grow into columnar nanocrystals, further improving the wear resistance and corrosion resistance of the composite sheet. The thickness of the surface layer 120 is preferably set to 100-600nm. When the thickness of the surface layer 120 is within the above-mentioned predetermined thickness range, the top of the grain 121 can grow a protrusion 122, so that the surface of the surface layer 120 forms a nano-scale concave-convex structure. More preferably, the thickness of the surface layer 120 is preferably set to 300-500nm.
[0136] refer to Figure 7a-7d The cross-sectional morphology of the surface layer 120 at different growth thicknesses is shown. Figure 7a The cross-sectional morphology is shown when the thickness of the surface layer 120 is 50 nm. Figure 7b The cross-sectional morphology when the thickness of the surface layer 120 is 100 nm is shown. Figure 7c The cross-sectional morphology is shown when the thickness of the surface layer 120 is 400 nm. Figure 7d The cross-sectional morphology when the thickness of the surface layer 120 is 600nm is shown. It can be seen from the figure that when the thickness of the surface layer 120 is 50nm, the top of the grain 121 cannot grow a protrusion 122, and the surface of the surface layer 120 forms a flat surface. As the deposition thickness of the surface layer 120 increases, when the thickness is greater than 100nm as shown in the figure, the top of the grain 121 gradually grows a protrusion 122, and the protrusion 122 becomes more obvious and fuller as the deposition thickness increases. However, when the deposition thickness of the surface layer 120 increases from 400nm to 600nm, the protrusion 122 at the top of the grain 121 tends to be flattened. It can be seen that when the deposition thickness of the surface layer 120 exceeds 600nm, the protrusion 122 at the top of the grain 121 continues to be flattened, which will make the concave-convex structure less obvious.
[0137] Further preferably, copper element can be added to the surface layer 120 to further improve the non-stick performance. For example, the surface layer 120 is a titanium carbonitride-copper composite layer, a chromium carbonitride-copper composite layer or a zirconium carbonitride-copper composite layer. Since copper does not react with carbon and nitrogen elements, and cannot form a solid solution with carbonitride, but exists in an amorphous form, during the physical vapor deposition process, the amorphous copper is coated outside the columnar nanocrystalline structure of the grain 121, inhibiting the growth of the grain 121, so that the grain 121 will be smaller, effectively reducing the surface energy, and further improving the non-stick and easy-to-clean performance of the composite sheet.
[0138] Preferably, if Figure 5 and Figure 6As shown, the coating 150 also includes a transition layer 130, the surface layer 120 is attached to the transition layer 130, and the above-mentioned grains 121 grow in a direction perpendicular to the surface of the transition layer 130. The transition layer 130 includes a first transition layer 131 and a second transition layer 132, and the first transition layer 131 and the second transition layer 132 are alternately stacked. Among them, the first transition layer 131 is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer. The second transition layer 132 is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer. The second transition layer 132 is different from the first transition layer 131. The thickness of the first transition layer 131 and the second transition layer 132 are both 10-50nm, and the total thickness of the transition layer 130 is 300-1000nm.
[0139] The transition layer 130, which is an alternating arrangement of two material layers formed by titanium, chromium and zirconium base and their compounds, can produce a template effect on the growth of the columnar nanocrystalline structure, causing lattice distortion, thereby inhibiting the growth of coarse columnar nanocrystals in the surface layer 120, and causing the columnar grains 121 to tend to grow perpendicular to the crystal plane, thereby reducing the surface energy of the surface layer 120, forming a fine and dense columnar nanocrystalline structure, making the composite sheet have good non-stickiness and easy cleaning properties, and as the density of the surface layer 120 increases, its hardness and corrosion resistance are also improved, so as to better protect the concave and convex marking area.
[0140] Further preferably, the coating 150 further includes a bottom layer 140, the bottom layer 140 is attached to the surface of the metal substrate 110, the transition layer 130 is attached to the bottom layer 140, and the bottom layer 140 is a metal layer. The bottom layer 140 is preferably a titanium metal layer, a chromium metal layer, a zirconium metal layer, a chromium-titanium composite metal layer, a chromium-zirconium composite metal layer or a zirconium-titanium composite metal layer. The thickness of the bottom layer 140 is 100-500nm. Thus, the metal bottom layer 140 can increase the bonding force between the coating 150 and the metal substrate 110, so that the coating 150 is not easy to fall off from the metal substrate 110, thereby increasing the service life.
[0141] Preferably, the total thickness of the coating 150 including the surface layer 120, the transition layer 130 and the bottom layer 140 is 700-2000nm, preferably 800-1600nm. Further preferably, the total thickness of the coating 150 is 1100-1300nm. Referring to Table 1, the performance test of embodiments with different thicknesses of the coating 150 is shown. Among them, the experimental steps of the easy-to-clean performance of rice are as follows: (1) Add rice and water according to the type and volume of different cooking utensils; (2) Turn on the power to cook, and keep warm for 10 minutes after the cooking is completed; (3) Invert the cooking utensil and observe whether all the rice falls off by gravity or gently shaking the inner pot; (4) After cleaning the cooking utensil, repeat the above experiment for a total of 5 times to check the easy-to-clean performance of the cooking utensil, and determine the evaluation level of the rice residue according to the average weight of the residue in the last 4 times. The evaluation standards for the ease of cleaning of rice are as follows: Level 1: Lightly shake the cooking utensil or without shaking, and all the rice can fall off the utensil; Level 2: Lightly shake the cooking utensil, and there is still rice stuck to the inner pot, and the weight of the rice is ≤50g; Level 3: Lightly shake the cooking utensil, and there is still rice stuck to the inner pot, and the weight of the rice is 50g<rice weight≤100g; Level 4: Lightly shake the cooking utensil, and there is still rice stuck to the inner pot, and the weight of the rice is>100g.
[0142] Table 1
[0143]
[0144] The hardness of the coating 150 increases with the increase of the total thickness, while the bonding force between the coating 150 and the metal substrate 110 increases first and then decreases with the thickness, especially when the total thickness is greater than 2000 nm, the bonding force drops sharply.
[0145] For example, as a first optional embodiment, the surface layer 120 is a titanium carbonitride layer, the first transition layer 131 and the second transition layer 132 are respectively a titanium carbonitride layer and a chromium carbonitride layer, and the bottom layer 140 is a chromium-titanium composite metal layer. As a second optional embodiment, the surface layer 120 is a zirconium carbonitride layer, the first transition layer 131 and the second transition layer 132 are respectively a zirconium carbonitride layer and a chromium carbonitride layer, and the bottom layer 140 is a chromium-zirconium composite metal layer. As a third optional embodiment, the surface layer 120 is a chromium carbonitride layer, the first transition layer 131 and the second transition layer 132 are respectively a zirconium carbonitride layer and a titanium carbonitride layer, and the bottom layer 140 is a titanium-zirconium composite metal layer.
[0146] In order to further improve the bonding force between the surface layer 120 and the transition layer 130, the surface layer 120 and the first transition layer 131 or the second transition layer 132 in the transition layer 130 that contacts the surface layer 120 contain the same carbon nitride compound, for example, refer to the first optional embodiment and the second optional embodiment described above. In order to further improve the bonding force between the transition layer 130 and the bottom layer 140, the bottom layer 140 and the first transition layer 131 or the second transition layer 132 in the transition layer 130 that contacts the bottom layer 140 contain the same metal element, for example, refer to the first optional embodiment and the third optional embodiment described above.
[0147] The optional combination of each layer can also be: as a fourth optional embodiment, the surface layer 120 adopts a titanium carbonitride-copper composite layer, the first transition layer 131 and the second transition layer 132 are selected from a titanium carbonitride layer and a chromium carbonitride layer, respectively, and the bottom layer 140 adopts a chromium-titanium composite metal layer. As a fifth optional embodiment, the surface layer 120 adopts a chromium carbonitride-copper composite layer, the first transition layer 131 and the second transition layer 132 are selected from a titanium carbonitride layer and a chromium carbonitride layer, respectively, and the bottom layer 140 adopts a chromium-titanium composite metal layer. As a sixth optional embodiment, the surface layer 120 adopts a zirconium carbonitride-copper composite layer, the first transition layer 131 and the second transition layer 132 are selected from a zirconium carbonitride layer and a chromium carbonitride layer, respectively, and the bottom layer 140 adopts a chromium-zirconium composite metal layer. As a seventh optional embodiment, the surface layer 120 adopts a chromium carbonitride-copper composite layer, the first transition layer 131 and the second transition layer 132 are selected from a zirconium carbonitride layer and a titanium carbonitride layer, respectively, and the bottom layer 140 adopts a titanium-zirconium composite metal layer.
[0148] The second aspect of the present application also provides an inner liner, which is made of the composite sheet of the first aspect. The inner surface of the inner liner is provided with the above-mentioned coating 150, so that the surface layer 120 of the coating 150 faces inward. Optionally, the outer surface of the inner liner can also be provided with the above-mentioned coating 150, and the surface layer 120 of the coating 150 faces outward. According to the inner liner of the present application, it is made of the composite sheet of the first aspect, and therefore has a technical effect similar to that of the composite sheet of the first aspect.
[0149] The third aspect of the present application also provides a cooking utensil. The cooking utensil includes a pot body and a cover body, and the cover body can be connected to the pot body. The pot body is basically in the shape of a rounded rectangular parallelepiped and has a cylindrical inner pot storage portion, and the inner pot can be freely placed in the inner pot storage portion or taken out from the inner pot storage portion to facilitate the cleaning of the inner pot. The inner pot is usually made of metal material and has a circular opening on the upper surface for holding materials to be heated, such as rice, soup, etc. The pot body may include a heating device for heating the inner pot.
[0150] The cover has a shape that is substantially corresponding to the pot body. The cover can be opened and closed on the pot body. Specifically, it is pivotally connected to the pot body via a pivot shaft and can freely pivot between a closed position and an open position relative to the pot body around a pivot axis where the pivot shaft is located, so as to facilitate the closing and opening of the pot body. When the cover is closed on the pot body, it covers the inner pot and forms a cooking space between the inner pot and the cover. The cooking utensil according to the present application has the inner pot of the second aspect above, and thus has a technical effect similar to that of the inner pot of the second aspect above.
[0151] The fourth aspect of the present application also provides a method for manufacturing a composite sheet. Fig.10 and Fig.11 As shown, the method for manufacturing the composite sheet includes a metal substrate preparation step S1 and a physical vapor deposition step S2.
[0152] Among them, the step of preparing the metal substrate S1 includes the step of forming a concave-convex marking area: a plurality of grooves 111 extending along a first direction are arranged on the surface of the metal substrate 110, and the plurality of grooves 111 are periodically arranged along a second direction to form a concave-convex marking area. The second direction is different from the first direction. The grooves 111 are formed into a concave-convex marking area by laser processing. After the step of forming the concave-convex marking area, the metal substrate 110 is placed in a physical vapor deposition device.
[0153] The physical vapor deposition step S2 is specifically to deposit the coating film 150 at least at the concave-convex marking area of the metal substrate 110. The physical vapor deposition step S2 includes a surface layer deposition step S23: growing the surface layer 120 of the coating film 150 into a columnar nanocrystalline structure by physical vapor deposition.
[0154] According to the present application, the combination of the concave-convex identification area and the columnar nanocrystal PVD coating of the composite sheet prepared by this manufacturing method can make the composite sheet have good non-stick, hydrophobic and easy-to-clean properties without setting a special non-stick coating, and also have high hardness and scratch resistance; the columnar nanocrystal structure can be directly formed on the surface of the metal substrate through physical vapor deposition without the need for additional steps.
[0155] Specifically, laser processing can use picosecond laser pulses or nanosecond laser pulses to prepare the concave-convex marking area in an arcuate filling manner, and can be specifically done by moving the metal substrate 110 or by moving the laser. The laser power is set to 10-100W and the scanning speed is 100-3000mm / s.
[0156] Furthermore, the step S1 of preparing the metal substrate also includes a polishing step and a cleaning step, in which the metal substrate 110 is polished and cleaned. The polishing step and the cleaning step are located before the step of forming the concave-convex marking area, so that the surface roughness of the metal substrate 110 is 0.1-0.8 μm.
[0157] Specifically, the polishing step can use a mechanical polishing process, an electrochemical polishing process, or a plasma polishing process to polish the metal substrate 110, and then perform a wire drawing process on the polished surface. The subsequent cleaning steps are ultrasonic cleaning, pure water cleaning, and drying in sequence.
[0158] Specifically, physical vapor deposition may be performed by magnetron sputtering, arc ion plating, etc. In this embodiment, the arc ion plating process is used to deposit the coating 150 at least on the concave-convex marking area of the metal substrate 110 .
[0159] More specifically, if Figure 8 and Fig. 9 As shown, a rotating frame 12, a first metal target 13 and a second metal target 14 different from the first metal target 13 are provided in a deposition furnace 11 of the physical vapor deposition device 10. The first metal target 13 and the second metal target 14 are arranged at intervals around the rotation axis of the rotating frame 12. The metal elements of the first metal target 13 and the second metal target 14 are selected from titanium, chromium or zirconium. For example, the first metal target 13 can be a titanium target, and the second metal target 14 can be a chromium target. The physical vapor deposition device 10 also has a carbon source and a nitrogen source, wherein the carbon source is preferably acetylene gas, and the nitrogen source is preferably nitrogen.
[0160] The step S1 of preparing the metal substrate includes: placing the metal substrate 110 on a rotating frame and making the surface of the metal substrate 110 to be deposited face away from the rotation axis.
[0161] The step S23 of depositing the surface layer also includes: opening one of the first metal target 13 and the second metal target 14, opening the carbon source and the nitrogen source, and depositing the surface layer 120 on the surface to be deposited of the metal substrate 110. The metal element of the first metal target 13 or the second metal target 14 reacts with the carbon source and the nitrogen source to form the surface layer 120. Specifically, the step S23 of depositing the surface layer also includes: setting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, setting the temperature of the deposition furnace to 280-300°C, applying a bias voltage of 140-160V to the metal substrate 110 during deposition, and depositing for 10-30min to control the thickness of the surface layer 120 to be 100-600nm.
[0162] The physical vapor deposition step also includes a transition layer deposition step S22. The transition layer deposition step S22 is located before the surface layer deposition step S23, and the transition layer deposition step S22 includes: opening the first metal target 13 and the second metal target 14, and alternately depositing the first transition layer 131 and the second transition layer 132 on the surface to be deposited of the metal substrate 110 by rotation, wherein the metal elements of the first metal target 13 react with the carbon source and the nitrogen source to form the first transition layer 131, and the metal elements of the second metal target 14 react with the carbon source and the nitrogen source to form the second transition layer 132. According to the above process, the metal substrate 110 is alternately covered by the coating materials produced by the first metal target 13 and the second metal target 14 by rotation, so that the alternatingly stacked first transition layer 131 and the second transition layer 132 can be efficiently formed. Specifically, the step S22 of depositing the transition layer also includes: setting the temperature of the deposition furnace to 240-260°C, the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, applying a bias voltage of 140-160V to the metal substrate 110 during deposition, and depositing for 20-60 minutes to control the thickness of the transition layer 130 to be 300-1000nm.
[0163] The physical vapor deposition step also includes a bottom layer deposition step S21. The bottom layer deposition step S21 is located before the transition layer deposition step S22. The bottom layer deposition step S21 includes: opening the first metal target 13 and / or the second metal target 14, closing the nitrogen source and the carbon source, continuously introducing argon gas into the deposition furnace 11, and depositing the metal bottom layer 140 on the surface to be deposited of the metal substrate 110. This solution can use the same PVD equipment to deposit the metal bottom layer 140. Specifically, the bottom layer deposition step S21 also includes: setting the temperature of the deposition furnace to 200-450°C, glow cleaning the metal substrate for 3-7 minutes before deposition, applying a bias voltage of 50-250V to the metal substrate 110 during deposition, and depositing for 5-15 minutes to control the thickness of the bottom layer 140 to be 100-500nm.
[0164] In the physical vapor deposition step S2 , the rotation speed of the rotating frame 12 is set to 0.5-3 rpm to more effectively control the thickness of the coating film 150 and make the thickness distribution of the coating film 150 uniform.
[0165] Unless otherwise defined, the technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein are only for describing specific implementation purposes and are not intended to limit the present application. The features described herein in one embodiment may be applied to another embodiment individually or in combination with other features, unless the feature is not applicable or otherwise specified in the other embodiment.
[0166] The present application has been illustrated through the above-mentioned embodiments, but it should be understood that the above-mentioned embodiments are only for the purpose of example and explanation, and the present application is not limited to the above-mentioned embodiments. According to the teachings of the present application, more variations and modifications can be made, and these variations and modifications all fall within the scope of protection claimed by the present application.
Claims
1. A composite sheet, characterized in that: include: A metal substrate, wherein a surface of the metal substrate has a plurality of grooves extending along a first direction, wherein the plurality of grooves are periodically arranged along a second direction to form a concave-convex marking area, wherein the second direction is different from the first direction, and wherein the grooves are formed into the concave-convex marking area by laser processing; The coating is attached to the surface of the metal substrate by physical vapor deposition and covers the concave-convex marking area, wherein the coating includes a surface layer, and the surface layer is constructed as a columnar nanocrystal structure layer grown by physical vapor deposition.
2. The composite sheet according to claim 1, characterized in that: The depth of the groove before the coating is attached is greater than the depth of the groove after the coating is attached; and / or The depth of the groove before the coating is attached is 5-20 μm, and the depth of the groove after the coating is attached is 4-19 μm.
3. The composite sheet according to claim 1, characterized in that: The cross-section of the concave-convex marking area is in a tooth shape, and a spacer is formed between two adjacent grooves.
4. The composite sheet according to claim 3, characterized in that: The width of the groove before the coating is attached is greater than the width after the coating is attached, and the width of the spacer before the coating is attached is less than the width after the coating is attached.
5. The composite sheet according to claim 4, characterized in that: The width of the groove before the coating is 5-30 μm, and the width of the groove after the coating is 4-28 μm; The width of the spacer before being attached to the coating film is 5-30 μm, and the width of the spacer after being attached to the coating film is 7-32 μm.
6. The composite sheet according to claim 1, characterized in that: The cross-section of the concave-convex marking area is wavy, and the distances between adjacent wave peaks are equal before and after the coating film is attached.
7. The composite sheet according to claim 6, characterized in that: The distance between adjacent wave peaks is 5-30 μm.
8. The composite sheet according to claim 1, characterized in that: The surface roughness of the metal substrate is 0.1-0.8 μm.
9. The composite sheet according to claim 1, characterized in that: The columnar nanocrystal structure in the surface layer has multiple grains growing in a columnar shape, and the side surfaces of the multiple grains are attached to each other. When the surface layer is at a predetermined thickness, the top ends of the grains grow to form protrusions, so that the surface structure of the surface layer is a nano-scale concave-convex structure.
10. The composite sheet according to claim 9, characterized in that: The radial size of the grains is 20-80 nm; and / or The predetermined thickness of the surface layer is 100-600 nm.
11. The composite sheet according to any one of claims 1 to 10, characterized in that: The coating further includes a transition layer, the surface layer is attached to the transition layer, the transition layer includes a first transition layer and a second transition layer, and the first transition layer and the second transition layer are alternately stacked.
12. The composite sheet according to claim 11, characterized in that The coating also includes a bottom layer, the bottom layer is attached to the surface of the metal substrate, the transition layer is attached to the bottom layer, and the bottom layer is a metal layer.
13. The composite sheet according to claim 12, characterized in that: The thickness of the first transition layer is 10-50 nm, the thickness of the second transition layer is 10-50 nm, and the total thickness of the transition layers is 300-1000 nm; and / or The thickness of the bottom layer is 100-500 nm; and / or The total thickness of the coating is 700-2000nm.
14. The composite sheet according to any one of claims 1 to 10, characterized in that: The surface layer is a titanium carbonitride layer, a chromium carbonitride layer or a zirconium carbonitride layer.
15. The composite sheet according to any one of claims 1 to 10, characterized in that: The surface layer is a titanium carbonitride-copper composite layer, a chromium carbonitride-copper composite layer or a zirconium carbonitride-copper composite layer.
16. The composite sheet according to claim 15, characterized in that Amorphous copper encapsulates the grains of the columnar nanocrystalline structure.
17. The composite sheet according to claim 11, characterized in that: The first transition layer is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer; The second transition layer is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer; The second transition layer is different from the first transition layer.
18. The composite sheet according to claim 12, characterized in that: The bottom layer is a titanium metal layer, a chromium metal layer, a zirconium metal layer, a chromium-titanium composite metal layer, a chromium-zirconium composite metal layer or a zirconium-titanium composite metal layer.
19. A liner, characterized in that: The liner comprises a composite sheet according to any one of claims 1-18.
20. A cooking utensil, characterized in that: include: A pot body, wherein the pot body is provided with the inner pot according to claim 19; The cover body is openably and closably arranged on the pot body. When the cover body covers the pot body, a cooking space is formed between the cover body and the inner pot.
21. A method for manufacturing a composite sheet, characterized in that: The method for manufacturing the composite sheet comprises: The step of preparing a metal substrate comprises: The step of forming the concave-convex marking area is as follows: a plurality of grooves extending along a first direction are arranged on the surface of the metal substrate, the plurality of grooves are periodically arranged along a second direction to form the concave-convex marking area, the second direction is different from the first direction, the grooves are formed into the concave-convex marking area by laser processing, placing the metal substrate in a physical vapor deposition apparatus; The physical vapor deposition step deposits a coating at least at the concave-convex marking area of the metal substrate, and the physical vapor deposition step includes a surface deposition step: the surface layer of the coating is grown into a columnar nanocrystalline structure by physical vapor deposition.
22. The manufacturing method according to claim 21, characterized in that: The laser processing adopts picosecond laser pulses or nanosecond laser pulses.
23. The manufacturing method according to claim 22, characterized in that: Set the laser power to 10-100W and the scan speed to 100-3000mm / s, and / or The laser processing adopts an arcuate filling method.
24. The manufacturing method according to claim 21, characterized in that: The step of preparing the metal substrate further includes a polishing step and a cleaning step before the step of forming the concave-convex marking area, wherein the metal substrate is polished and cleaned so that the surface roughness of the metal substrate is 0.1-0.8 μm.
25. The manufacturing method according to claim 24, characterized in that: The metal substrate is polished by mechanical polishing, electrochemical polishing and plasma polishing, and then the polished surface is subjected to wire drawing, and then ultrasonic cleaning, pure water cleaning and drying are performed in sequence.
26. The manufacturing method according to any one of claims 21 to 25, characterized in that: The deposition furnace of the physical vapor deposition device is provided with a rotating frame, a first metal target and a second metal target different from the first metal target, wherein the first metal target and the second metal target are arranged at intervals around the rotation axis of the rotating frame, the metal elements of the first metal target and the second metal target are selected from titanium, chromium or zirconium, and the physical vapor deposition device further has a carbon source and a nitrogen source; The step of preparing the metal substrate comprises: placing the metal substrate on the rotating frame and making the surface to be deposited of the metal substrate face away from the rotating axis; The step of depositing the surface layer also includes: opening one of the first metal target and the second metal target, opening a carbon source and a nitrogen source, and depositing the surface layer on the surface to be deposited of the metal substrate, wherein the metal element of the first metal target or the second metal target reacts with the carbon source and the nitrogen source to form the surface layer.
27. The manufacturing method according to claim 26, characterized in that: The physical vapor deposition step also includes a transition layer deposition step, which is located before the surface layer deposition step, and the transition layer deposition step includes: opening the first metal target and the second metal target, and alternately depositing the first transition layer and the second transition layer on the surface to be deposited of the metal substrate by rotation, wherein the metal elements of the first metal target react with the carbon source and the nitrogen source to form the first transition layer, and the metal elements of the second metal target react with the carbon source and the nitrogen source to form the second transition layer.
28. The manufacturing method according to claim 27, characterized in that: The physical vapor deposition step also includes a bottom layer deposition step, which is located before the transition layer deposition step. The bottom layer deposition step includes: opening the first metal target and / or the second metal target, closing the nitrogen source and the carbon source, continuously introducing argon gas into the deposition furnace, and depositing a metal bottom layer on the surface to be deposited of the metal substrate.
29. The manufacturing method according to claim 26, characterized in that: The carbon source is acetylene gas, and the nitrogen source is nitrogen gas; The step of depositing the surface layer also includes: setting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, setting the temperature of the deposition furnace to 280-300°C, applying a bias voltage of 140-160V to the metal substrate during deposition, and depositing for 10-30 minutes to control the thickness of the surface layer to 100-600nm.
30. The manufacturing method according to claim 27, characterized in that: The carbon source is acetylene gas, and the nitrogen source is nitrogen gas; The step of depositing the transition layer also includes: setting the temperature of the deposition furnace to 240-260°C, setting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, applying a bias voltage of 140-160V to the metal substrate during deposition, and depositing for 20-60 minutes to control the thickness of the transition layer to 300-1000nm.
31. The manufacturing method according to claim 28, characterized in that: The deposition of the bottom layer also includes: setting the temperature of the deposition furnace to 200-450°C, glow cleaning the metal substrate for 3-7 minutes before deposition, applying a bias voltage of 50-250V to the metal substrate during deposition, and depositing for 5-15 minutes to control the thickness of the bottom layer to 100-500nm.